(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article analyzes offenses related to the failure to comply with the legal demands of law enforcement officers, their types, and the administrative liability associated with them. The article examines the forms of offenses such as failure to present documents, failure to identify individuals, failure to stop vehicles, and failure to provide assistance to victims. Furthermore, the importance of research on the key characteristics of such offenses and their various forms in the legislation is emphasized.